Phosphate solubilization and synergism between P-solubilizing and arbuscular mycorrhizal fungi - Souchie, Edson Luiz; Azcón, Rosario; Barea, Jose Miguel; Saggin-Júnior, Orivaldo José; da Silva, Eliane Maria Ribeiro (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the ability of several P-solubilizing fungi to solubilize aluminum phosphate and Araxá apatite as well as the synergism between the P-solubilizing fungus, PSF 7, and arbuscular mycorrhizal fungi to promote clover growth amended with aluminum phosphate. Two experiments were carried out, the first under laboratory conditions and the second in a controlled environmental chamber. In the first experiment, PSF 7, PSF 9, PSF 21 and PSF 22 isolates plus control were incubated in liquid medium at 28ºC for eight days. On the 2nd, 4th and 8th day of incubation, pH and soluble P were determined. In the second experiment, clover was sowed in plastic pots containing 300 g of sterilized substrate amended with aluminum phosphate, 3 g L-1, in presence and absence of PSF 7 isolate and arbuscular mycorrhizal fungi. A completely randomized design, in factorial outline 2x2 (presence and absence of PSF 7 and arbuscular mycorrhizal fungi) and five replicates were used. In the first experiment, higher P content was detected in the medium containing aluminum phosphate. PSF 7 is the best fungi isolate which increases aluminum solubilization with major tolerance to Al3+. Clover growth was stimulated by presence of PSF 7 and arbuscular mycorrhizal fungi. There is synergism between microorganisms utilized to improve plant nutrition.